The experience of rational development of hydrocarbon resources in the Earth’s interior used in the new paradigm of Academician A.E. Kontorovich – the development of oil and gas complex of Russia - Renat Kh. Muslimov (Georesursy, 2020)
The Republic of Tatarstan has accumulated vast experience in the exploration and development of oil fields of various ranks – from small and smallest to giant and supergiant. Approaches for the rational development of various groups and categories of deposits have been found. The most effective methods of prospecting, exploration and additional exploration of oil fields, the most advanced hydrodynamic methods of developing fields with active and hard-to-recover reserves, including those at the late and post-late stages of development, have been worked out. Methods of enhanced oil recovery have found wide application for various geological and physical conditions, including the extraction of residual reserves from long-term exploited fields. A great deal of experience has been accumulated in the development of complex small fields with hard-to-recover oil reserves. Research work is underway to find effective methods for the development of unconventional oil deposits (high-viscosity, ultra-high-viscosity oils and natural bitumen, in shale and similar deposits), to study the phenomenon of replenishment of sedimentary cover deposits with deep hydrocarbons through the crystalline basement. This experience of advanced development of the republic helps in the formation of the principles of a new paradigm for the development of the oil and gas industry.